Improved High Frequency Pulse Injection Control Inlow Speed Domain of Permanent Magnet Synchronous Motor - LU De-gang; JIANG Guo-wei; JI Tang-long (Journal of Harbin University of Science and Technology, 2022)
Abstract:For zero cases at low speed, high frequency pulse vibration injection of sensorless permanent magnet synchronous motor control system in the rotor position information extraction problem of error signal, and second-order generalized integrator is proposed to replace the traditional control method adopted by the low-pass filter for rotor position information extraction, and combining the immunity control method, improve to the accuracy of high frequency pulse vibration injection method. Taking the actual frequency of the extracted signal as the input quantity, the table-mounted permanent magnet synchronous motor was selected, and the traditional motor double closed-loop control combined with field directional control was used for simulation. Selecting DSP minimum system board as panel, in combination with the driven plate and motor set up experimental platform experiment, by comparing the results before and after improvement, it is concluded that the improved control method can better reduce the speed and rotor position information error, making the motor estimated speed and rotor position closer to a given value conclusion.